LEARNING OPPORTUNITIES IN THE PRESENT SCENARIO - Kaur, Navdeep (INTERNATIONAL JOURNAL OF RESEARCH IN EDUCATION METHODOLOGY, 2013)
Learning is a natural process. It is spontaneous to a child, nurtured by a ' variety of interactions at home, in school and within the community. The child !earns through one's own experiences as well as from the experiences of others. The child acquires these experiences by involving in simple activities. Doing or engaging in such activities plays an important part in cognitive development of the child. Learning gets accelerated when the child gets adequate opportunities to explore, experiment, assemble and dismantle things freely, commit mistakes and learn from the mistakes Seen in this perspective, learning is an active. reflective and interactive phenomenon within a social context. Direct involvement of the child in actions extends understanding, helps develop intellectual faculties and development achieved through active participation leads to further expression in the form of more and more activities. Learning occupies a very important place in our life. Most of our behaviour is mainly influenced by what we learn and how we learn it. It is a life long process that involves Constant change, adjustment and development. Out instincts, attitudes, appreciations, skills find abilities are primarily the product of learning. Learning implies acquisition of knowledge and skills on one hand, modification of behaviour on the other hand. It is measured in terms of improvement of behaviour.